ASUHAN KEPERAWATAN JIWA PADA TN. D DENGAN MASALAH UTAMA HARGA DIRI RENDAH DI PUSKESMAS SINDANGKASIH CIAMIS - Asep Riyana; Abdul Kholiq Masrurii (Poltekkes Kemenkes Tasikmalaya, 2023)
This scientific paper is motivated by the number of cases of Low Self-Esteem Disorders in the working area of ​​the Sindangkasih Public Health Center in Ciamis Regency in 2019 were 28 cases, the number has increased from the previous year in 2018 of 23 cases. The number is still uncertain because there are still those who are not ready to go to the Puskesmas so that it will definitely increase in the following year after the data collection (Sindangkasih Puskesmas, Ciamis Regency, 2019). Based on this phenomenon, the role of nurses is very important in providing nursing care. In accordance with the duties of nurses, namely nursing care givers. The purpose of writing this Scientific Paper is to provide nursing care to clients with low self-esteem issues in the working area of ​​the Sindangkasih Health Center in Ciamis Regency. The method used in writing this Scientific Writing is a qualitative descriptive in the form of a case report. At the time of conducting the assessment process, the authors found symptoms that were consistent with the theory of signs of low self-esteem symptoms in the client, including not daring to stare at the other person, more down, lowering the productivity of the client, and dressing neatly. Data collection techniques used by means of interviews, physical examinations, observation and study of documentation and nursing process include assessment, diagnosis, planning, implementation, and evaluation. Nursing diagnoses that arise are low self-esteem, social isolation, and self-care deficits.